Fucose Migration Pathways Identified Using Infrared Spectroscopy. (14th March 2023) - Moge, Baptiste; Schindler, Baptiste; Yeni, Oznur; Compagnon, Isabelle
Abstract: Fucose is a ubiquitous monosaccharide associated to major classes of glycans. A main obstacle to the sequencing of fucosylated glycans is the migration of fucose, which leads to misinterpretations in mass spectrometry analysis. Here, using ion vibrational spectroscopy, we resolve the structure of fucosylated fragments of Lewis and blood group H antigen trisaccharides and we unveil the position and linkage of the fucose after migration. Our findings demonstrate that the structure of fragment ions resulting from fucose migration can be characterized. Additionally, we report a new type of fucose migration, which does not feature any change of mass and therefore had not been previously reported: it consists of a local migration where the fucose changes its position remaining on the initial residue. Our approach allows the characterization of glycans, an essential step to interpret glycomics data, as well as to understand underlying processes at play in mass spectrometry. Abstract : The mass‐spectrometric study of fucosylated oligosaccharides is arduous due to the propensity of fucose to migrate in the gas phase—especially during the collision‐induced dissociation step (but not always). Gas‐phase infrared spectroscopy has shown its potential to identify fucose migration products. The investigations have also shown a new type of migration.